Pembinaan Kemandirian Anak Asuh Di Panti Asuhan Chairun Nissa - Nadira Choirunnisa; Desy Safitri; Martini Martini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to: (1) Describe the development of independence for foster children at the Chairun Nissa Orphanage. This research was conducted at the Chairun Nissa Orphanage on JL. Pisangan Baru Timur, No.12, Jatinegara, RT.6/RW.15, Pisangan Baru, Kec.Matraman, East Jakarta City, Special Capital Region of Jakarta 13110. The research method used was descriptive with a qualitative approach. Data collection techniques through observation, interviews, documentation and literature study. The subjects in this research were 8 respondents. The results of this research show that: (1) The process of fostering caregivers in forming the independence of foster children at the Chairun Nissa Orphanage in the coaching that is carried out includes several steps such as modeling, providing attention and love, providing good lessons (advice), and providing rewards and punishments. Coaching consists of several forms such as physical coaching, cultural coaching, religious coaching, and intellectual coaching. Chairun Nissa Orphanage Caretakers have a role in forming the independence of foster children in 3 aspects, namely emotional independence (emotional autonomy), independence in behavior (behavioral autonomy), and independence in values ​​(value autonomy).